Extended applications of molecular dynamics methods in multiscale studies of concrete composites: A review - Jie Cao; Chao Wang; Jaime Gonzalez-Libreros; Tongfang Wang; Yongming Tu; Lennart Elfgren; Gabriel Sas (Case Studies in Construction Materials)
This paper investigates the current landscape of multiscale studies in concrete composites incorporating molecular dynamics (MD) methods. Through a thorough literature analysis, it was determined that finite element, discrete element, homogenization, microphysical characterization, and machine learning methods are better suited for integration with MD in multiscale studies of concrete composites. The paper delves into MD's application characteristics and the selection of force fields in multiscale studies and provides a summary of the combined applications between MD and various methods. Challenges identified include the optimization of MD simulations and the appropriate selection of combined methods. The conclusions underscore the growing recognition of MD's significance, advocating for rational multi-method integration in multiscale approaches to effectively advance research on concrete composites.